Fatal outcome of a hypersensitivity reaction to paclitaxel: a case report - P. van Meerbeeck, Jan; S. Kloover, Jeroen; A. den Bakker, Michael (Contemporary Oncology/Współczesna Onkologia, 2002)
Hypersensitivity reactions (HSRs) to paclitaxel are frequently encountered in patients receiving this anti-tumor drug. Oral pre-medication with dexamethasone at a dose of 20 mg and given orally at 12 and 6 hours before infusion of paclitaxel have been shown to reduce the incidence of paclitaxel-induced HSRs significantly. However, due to logistic factors, short-course pre-medication with intravenously administered dexamethasone given 30 minutes prior to paclitaxel infusion became customary and retrospective analysis showed that this pre-medication schedule was as effective as the oral regimen. In this case report we describe the fatal outcome of a HSR in a patient receiving paclitaxel despite short-course pre-medication. The level of evidence supporting the short-course iv pre-medication schedule is challenged, as it is not compatible with the pharmacokinetic properties of dexamethasone.